The Use of Facebook in Educational Communication among University Students: Determinants and Academic Achievement - Kumari, Nisha Kumari; Jabeen, Saima (PJE, 2024)
The increasing prevalence of social networking sites (SNS) in students' daily lives has prompted investigations into their tangible impact on academic contexts. This research delves into the intricacies of students' utilization of Facebook for educational communication and the subsequent impact on academic achievements. A cross-sectional survey, employing a customized questionnaire, was conducted among Facebook users across four universities in Karachi. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study rigorously examined the hypotheses embedded in the research model. The findings underscore that the adoption of Facebook for educational communication is significantly influenced by subjective norms and purposive value. Importantly, a positive correlation emerged between the use of Facebook for educational purposes and the perceived academic achievements of a diverse student cohort. These results yield valuable insights for higher education institutions and educators, highlighting the potential positive consequences associated with integrating Facebook into higher educational learning environments. Recognizing the pivotal role of social media in education, this research contributes to anuanced understanding of factors influencing students' engagement with Facebook and its implications for academic success in diverse university settings.